Alternative development in the proposed model of the Strategy for Empowerment and Spatial Sustainable Development/ Baghdad Governorate Council as a case study (Journal of Planner and Development, 2021)
This research mainly aims to analyze local development strategy in Baghdad Governance, build the Strategic Model based on the study area’s spatial interaction, and achieve the Trinity of Excellence based on the global model of excellence. This research applied SWOT strategic analysis for the strengths and weaknesses of the internal environment and opportunities and threats of the external environment for the provincial council. In conclusion, the research specifies appropriate alternatives and choosing the best in line with the reality of the Baghdad Provincial Council. Also, the strategic goals in the national plan and the spatial interaction of the development goals, and the Empowerment Strategy that takes the vision and modern philosophy in planning (Out-Box) and makes the human dimension the base assets of development.